El recurso agua : ¿Futuro foco de conflicto en el Medio Oriente? - Tressler Zamorano, Frank McShane (Estudios Internacionales, 1994)
In light of the extensive problems that the Middle East has with respect to water resources, unless there are profound changes in the implementation of a uniform policy regarding its control and distribution, this could be the cause of a new focus of conflict in the region. In this papers it is argued that it is of utmost importance that behind the solution to this problem must be the concept of sustainable development, which must necessarily contemplate the protection of the environment. However, the projects that are currently being carried out do not address this issue in a comprehensive way, but have instead intensified the differences. In this sense, the United States must assume a leadership role and some solutions are suggested that involve technological innovations, diplomatic actions, and the participation of related international organizations.